Analisis Kesulitan Belajar Siswa Sekolah Dasar dalam Memahami Materi Kubus - Suci Amalia Putri; Herawati Purba; Zikra Anastasya Az-Zahra; Victory Bangun; Elvi Mailani; Nur Rarastika (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research discusses the analysis of students' learning difficulties in understanding cube building material. Mathematics is a basic science that must be studied from an early age because it is closely related to other sciences in order to advance to the next level. The research was created to solve students' learning difficulties at SD Negeri 104208 Cinta Rakyat. This research uses a qualitative approach with descriptive research type. The results obtained are that students still lack understanding of the material that has been presented by the teacher in the process of teaching and learning activities, there are many students who do not understand the material explained by the teacher. It can be seen that students' learning difficulties are also determined by low interest in learning and Lack of understanding of the material taught. Several factors include disinterest in mathematics and ineffective use of learning media. This research suggests that schools are expected to innovate in the use of learning media and learning methods that are changed and adapted to students' learning needs and interests.